Kenya - Briggs, Philip; Briggs, Philip; Williams, Lizzie (London : Dorling Kindersley Ltd., 2013)
DK Eyewitness Travel Guide: Kenya will lead you straight to the best attractions this country has to offer. Packed with full-color photography, illustrations, and maps, this updated guide explores Kenya's many dynamic features, from the spectacular wildlife and breathtaking national parks, to the lively nightlife and cultural attractions of Nairobi. Features include a comprehensive illustrated guide to Kenya's habitats and wildlife, information on game reserves and safaris, and detailed maps of Kenya's national parks. DK Eyewitness Travel Guide: Kenya provides all the insider tips visitors need with listings of the best hotels, restaurants, bars, and shops for all budgets, as well as the entertainment, beaches, markets, and festival options listed town by town. Now available in PDF format.
Intro -- Contents 4 -- How to Use This Guide 6 -- Discovering Kenya 10 -- Putting Kenya on the Map 12 -- A Portrait of Kenya 14 -- Kenya Through the Year 38 -- The History of Kenya 42 -- The Safari Experience 58 -- Habitats 80 -- Field Guide 96 -- Kenya at a Glance 148 -- Nairobi 150 -- Southeastern Savannahs 176 -- Southern Coast 198 -- Northern Coast 226 -- Southern Rift Valley and Masai Mara 252 -- Western Kenya 284 -- Central Highlands 308 -- Northern Kenya 334 -- Where to Stay 358 -- Where to Eat 378 -- Shopping in Kenya 390 -- Entertainment in Kenya 396 -- Outdoor Activities 398 -- Practical Information 408 -- Travel Information 420 -- General Index 428 -- Acknowledgments 442 -- Phrase Book 446.
Includes index.
"ISSN: 1542-1554."
English
Description based on publisher supplied metadata and other sources.
Keywords: Kenya -- Guidebooks; Kenya -- Description and travel